Litigasi Hybrid Contract Gadai pada Lembaga Keuangan Syariah - Sirajul Arifin (Islamica: Jurnal Studi Keislaman, 2018)
The article examines the hybrid contract that is still debated although the contract has framed pawn products in Islamic financial institutions. The pawn system which has been regulated by the DSN-MUI, however, still leaves a problem. The problem arises because the mortgage system is a combination system of several contracts that require collateral. Collateral is used to build bank trust and the customer’s responsibility that the customer will return the loan in accordance with the contract. The used contracts are the loan, mortgage and lease agreements. If the financing in the mortgage system is default, the collateral item becomes the compensation for the repayment of the remaining debt of the customer. Pawn systems that require sublimation of several contracts in pawn products still become a subject of criticism. Hadiths about the prohibition of bay‘ and salaf, prohibitions requiring additional debt, and the prohibition of charging fees for collateral are those that criticize and are not aware of pawn hybrid contract. Even though the pawn hybrid contract is still criticized, the demand for contemporary transactions in sharia financial institutions cannot be ignored, even its presence is a necessity as long as it does not violate sharia norms and values.